Manfaat dan Kesenjangan Alat Pendidikan di Era Digital - Rafni Melisa Putri; Ratna Sari; Uswatun Hasanah; Zaqqi Habibillah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Educational programs are one of the crucial pillars in human life. Through education, individuals can acquire fundamental knowledge, skills, and attitudes to face various challenges in life. In addition, education also has a central role in shaping the character of the nation's children, creating individuals who are able to contribute to society. In the context of education, the use of educational support tools is a critical aspect that needs attention. Educational support tools include devices and materials that support the effectiveness and efficiency of the teaching and learning process. Its function involves delivering information in an interesting and interactive manner, facilitating the understanding of the material by learners, and increasing their active involvement in learning. However, along with technological advances, educational tools are experiencing rapid development. This provides opportunities for learning that are more accessible to various groups. However, challenges arise in the form of educational gaps. Schools in remote areas, for example, may face limited access to the internet, computers, or mobile devices that are essential to the learning process. Therefore, the role of educational tools is crucial in creating inclusive education, overcoming gaps, and ensuring that every individual can access learning in this digital era.